Measuring Emotional Resonance Experience: An Exploratory Analysis Among F&B Cashew Consumers In Indonesia - Timothy Jason Lianto (Bina Nusantara University, 2026)
This study aims to definitely identify and validate the fundamental factors that form the Emotional Resonance Experience in consumers. Design/methodology/approach: This study used a quantitative method by distributing questionnaires via Google Form. The total sample of the study was 121 respondents who were consumers of Renjana Cashew. Using SPSS, Exploratory Factor Analysis (EFA) was employed to analyze the data and to determine the factors that form the Emotional Resonance Experience. The results of the study show that five factors accounts for the Emotional Resonance Experience, namely emotional engagement, memorable experience, personal meaningfulness, personal relevance, and also reliability. These five factors collectively explain 93,168% of the total variance. Interestingly, EFA reveals that ERE is a multidimensional phenomenon structured not only by emotional bonds but also by personal cognitive relevance and product reliability which provide a strong foundation for stability and peace of mind. Originality/value (State of the art): The novelty of this research lies in the discovery and empirical validation of five specific, structured dimensions that effectively shape the identification of the complex mechanism required to create deep and sustainable emotional bonds, thereby providing a tested model ERE dimensions to enrich the literature on consumer behavior and experiential marketing.